La determinación obligatoria del Objeto Social: Una regla anacrónica - Montoya Stahl, Alfonso; Loayza Jordán, Fernando (Pontificia Universidad Católica del Perú, 2015)
The authors discussed on the alleged utility as well as the drawbacks of the mandatory determination of corporate purpose. They analyze and criticize the required characteristics of the corporate purpose by the Peruvian corporate regulation as well as the alleged benefits of making mandatory its determination. The authors propose the elimination of the obligation to determine the corporate purpose in order to give corporations freedom to configure their economic activity without being limited by an outdated rule.

En el presente artículo, los autores discuten la presunta utilidad como inconvenientes de la obligación de determinar el objeto social. En ese sentido, se analiza las características exigidas al objeto social, como los supuestos beneficios que traería su regulación. Los autores proponen la eliminación de la obligación de determinar el objeto social a fin de permitir a las sociedades configurar libremente su actividad, sin verse limitadas por una norma rígida.
The mandatory determination of the Corporate Purpose: An outdated rule
Keywords: Corporate Purpose; Ultra Vires Actions; General Corporations Law; Shareholders’ Interests; Public Interest; Objeto Social; Acto Ultras Vires; Ley General De Sociedades; Interés De Los Socios; Interés Público; https://purl.org/pe-repo/ocde/ford#5.05.00